2019
DOI: 10.1038/s41467-019-11561-7
|View full text |Cite
|
Sign up to set email alerts
|

A conserved regulatory program initiates lateral plate mesoderm emergence across chordates

Abstract: Cardiovascular lineages develop together with kidney, smooth muscle, and limb connective tissue progenitors from the lateral plate mesoderm (LPM). How the LPM initially emerges and how its downstream fates are molecularly interconnected remain unknown. Here, we isolate a pan-LPM enhancer in the zebrafish-specific draculin ( drl ) gene that provides specific LPM reporter activity from early gastrulation. In toto live imaging and lineage tracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 70 publications
6
86
0
Order By: Relevance
“…High levels of BMP signaling in the ventral domain of the embryo chiefly specifies the mesoderm territory that forms the LPM in all vertebrates (Ferretti and Hadjantonakis, 2019;Nishimatsu and Thomsen, 1998). Nonetheless, coinciding with Nodal activity, LPM-assigned cell fates also emerge along the marginal zone of Xenopus and zebrafish embryos that contribute the cells at the circumference of the forming embryo (Lane and Smith, 1999;Prummel et al, 2019;Schier and Talbot, 2005;Warga and Nüsslein-Volhard, 1999). Prominently shown in zebrafish embryos, an increasing range or activity of BMP signaling in ventralized mutants results in larger domains of LPM-expressed genes for erythrocyte, pronephros and vascular lineages (Hammerschmidt et al, 1996;Mullins et al, 1996;Sidi et al, 2003).…”
Section: Lpm Specification and Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of BMP signaling in the ventral domain of the embryo chiefly specifies the mesoderm territory that forms the LPM in all vertebrates (Ferretti and Hadjantonakis, 2019;Nishimatsu and Thomsen, 1998). Nonetheless, coinciding with Nodal activity, LPM-assigned cell fates also emerge along the marginal zone of Xenopus and zebrafish embryos that contribute the cells at the circumference of the forming embryo (Lane and Smith, 1999;Prummel et al, 2019;Schier and Talbot, 2005;Warga and Nüsslein-Volhard, 1999). Prominently shown in zebrafish embryos, an increasing range or activity of BMP signaling in ventralized mutants results in larger domains of LPM-expressed genes for erythrocyte, pronephros and vascular lineages (Hammerschmidt et al, 1996;Mullins et al, 1996;Sidi et al, 2003).…”
Section: Lpm Specification and Organizationmentioning
confidence: 99%
“…Following gastrulation, the LPM takes on its characteristic architecture: bilateral stripes ('plates') of LPM progenitors form laterally in the embryo and subsequently partition along the A-P and medial-to-lateral axes into dedicated cell fate domains (Gurdon, 1995;Kessler and Melton, 1994;McDole et al, 2018;Prummel et al, 2019). Convergent extension of the embryo axis involving planar cell polarity (PCP) signaling also affects the final position of the LPM adjacent to the forming somites ( paraxial mesoderm) and in relation to the ectoderm and the endoderm (Erter et al, 2001;Heisenberg and Solnica-Krezel, 2008;Saykali et al, 2019); however, LPM-specific mechanisms of cell arrangement have yet to be described in detail.…”
Section: Lpm Specification and Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lineage tracing studies in bony vertebrates (Chai et al, 2000;Jiang et al, 2002;Couly et al, 1993;Kague et al, 2012) have revealed that the pharyngeal arch skeleton derives largely from the neural crest -a vertebrate-specific, multipotent cell population that undergoes epithelial-to-mesenchymal transition from the dorsal neural tube, and that gives rise to a plethora of derivatives, including skeletal and connective tissue lineages (Green et al, 2015). The skeleton of paired appendages, on the other hand, derives from the lateral plate -a distinct mesodermal subpopulation that arose along the chordate stem (Prummel et al, 2019). As shared embryonic origin has classically been regarded as a key criterion for serial homology (discussed by Hall, 1995), Gegenbaur's gill arch hypothesis of paired fin origin was widely discounted, and is now generally deemed fundamentally flawed (Coates, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During embryogenesis, spatio-temporal expression patterns progress while a single totipotent cell differentiates and divides into the various lineages that comprise the adult body (Conklin, 1905, Sulston et al, 1983. Studies across deuterostome species revealed numerous highly conserved patterning pathways and transcription factors (Davidson et al, 2002, Farley et al, 2015, Krumlauf 1994, Prummel et al, 2019, Simakov et al 2015, Wodarz and Nusse 1998. Recently, advances in single-cell sequencing and lineage tracing have allowed high precision molecular and cellular timelines of the stem and progenitor cells involved in embryonic development and adult stem cell maintenance to be produced for chordates , Cao et al, 2019, Chan et al, 2018, Farrell et al, 2018, Nowotschin et al, 2019, Schaum et al, 2018.…”
Section: Introductionmentioning
confidence: 99%